Complete Genome Sequence of an Avian Metapneumovirus Subtype A Strain Isolated from Chicken (Gallus gallus) in Brazil - Rizotto, Lais S. (2017)
We report here the complete genome sequence of an avian meta-pneumovirus (aMPV) isolated from a tracheal tissue sample of a commercial layer flock. The complete genome sequence of aMPV-A/chicken/Brazil-SP/669/2003 was obtained using MiSeq (Illumina, Inc.) sequencing. Phylogenetic analysis of the complete genome classified the isolate as avian metapneumovirus subtype A.